Stereotipe Gen Z dalam Pekerjaan Daring sebagai Tutor Bahasa Asing: Prioritas Kesejahteraan Mental dan Persepsi terhadap Model Kerja Fleksibel - Diajeng Lieztianti (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to analyze how these stereotypes are formed and how mental well-being priorities and flexible working models are accepted in the context of online education. This research uses a qualitative approach with literature analysis of relevant studies on Gen Z characteristics in online work. The results show that although Gen Z is often perceived as less committed, they have high technological adaptability and tend to seek work-life balance to maintain teaching quality. Despite facing challenges in building interpersonal relationships and maintaining student motivation, their preferred flexible working model supports productivity and more effective teaching. This study suggests that it is important to change negative perceptions of Gen Z, by valuing their approach to mental well-being and use of technology in improving the quality of online education